The Effectiveness of Developing Contextual Material For Teaching English at Madrasah Aliyah - Enidar Enidar; Mukhaiyar Mukhaiyar; Z Mawardi Effendi; Zul Amri (Universitas Negeri Padang, 2018)
One of the aspects that determine the success of the learning process is teaching materials. This research aimed to develop the effectiveness of contextual material for teaching English at Madrasah Aliyah. The design of this research is development research by using ADDIE model. The product consists of two books, (teacher's book and students'book) the title is “English For Us”. Subjects in this research were all students of grade X. Sample were 87 persons and it was selected by using the purposive technique. The instrument used to collect data was a survey, questionnaires, and an interview. Data analysis was used the qualitative and quantitative technique. The practicalities of the teacher’s book were 82.54 and students’ book showed an average 84.63 score. The effectiveness of a product is measured through pre-test is 68,00 and post-test is 75.44. It can be concluded that the contextual material for teaching English at Madrasah Aliyah was effective